Penelope superciliaris pseudonyma Neumann, 1933 (Aves, Cracidae) is the valid name for the blue-faced population of Rusty-margined Guan endemic to the Madeira-Tapajós interfluvium of central Amazonian Brazil - Evangelista-Vargas, Diego; Costa, Thiago V. V.; Whitney, Bret M.; Schunck, Fabio; Silveira, Luís Fábio (Zootaxa, 2017)
As a part of a taxonomic study of the Penelope superciliaris complex, we noticed that two names are available for the population which occurs on the left margin of the Tapajós River, in Amazonian Brazil, which, in life, possesses a bright-blue face. The type locality of Penelope superciliares [sic] cyanosparius Nardelli, 1993, described by Nardelli (1993) based on living specimens, is not far from the type locality of P. s. pseudonyma Neumann, 1933. We collected new specimens across this region and, after a reexamination of the material used by Neumann (1933) to describe P. s. pseudonyma, we conclude that Penelope superciliaris pseudonyma is the oldest available name for the blue-faced guans restricted to the Madeira-Tapajós interfluvium, and P. superciliares [sic] cyanosparius Nardelli, 1993 must be treated as a junior synonym.